Ongelmallisen sosiaalisen median käytön yhteys koulutyön koettuun kuormittavuuteen yläkouluikäisillä suomalaisilla nuorilla – WHO-Koululaistutkimuksen tuloksia vuodelta 2022 - Minkkinen, Nea (2025)
In recent years, perceived schoolwork pressure has increased among Finnish adolescents. During secondary school, choices regarding the future become increasingly significant, and academic performance plays a growing role in determining future educational opportunities. At the same time, young people are spending more time on social media, which may reduce time available for schoolwork and shorten sleep duration – both of which can contribute to greater perceived pressure. The purpose of this study was to examine whether problematic social media use is associated with perceived schoolwork pressure. The study also explored how age, gender, social support, and morning tiredness influenced this association, and whether the connections differ between boys and girls.